FUNGSI LEGISLASI DPD DALAM SISTEM KETATANEGARAN INDONESIA - SETIO, STEVANUS EVAN (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013), 2013)
The legislative institution representing the majority of the people and the government is responsible to him. In order to reform the structure of the legislative institution in Indonesia into two rooms (bicameral) consisting of the House of Representatives (Dewan Perwakilan Rakyat (DPR)) and the Regional Representative Council (Dewan Perwakilan Daerah (DPD)). By the bicameral structure of the legislation process is expected to be held by double checking system that allow representation of the interests of all the people can be achieved relatively wider social base through. Legislation function, related to the authority determine, the rules that bind and restrict citizens to the legal norms. The Regional Representative Council (Dewan Perwakilan Daerah (DPD)) function, which is supposed to be a counterpart to the power of the House of Representatives (Dewan Perwakilan Rakyat (DPR)), looks no more than “accessories” representation system in Indonesia, which is still thick with unicameral system. Bicameral representation system adopted in the composition of representative institutions Indonesia can be categorized as a soft bicameral system. With a power as given by the constitution of Indonesia, the Regional Representative Council (Dewan Perwakilan Daerah (DPD)) as a representation of the regional people’s institution do not yet get the goal at the purpose of this institution establishment.
Keywords: The legislative institution; The Regional Representative Council; Legislation